Pengembangan Platform IoT Cloud berbasis Layanan Komputasi Serverless Google Cloud Platform (GCP) - Rizal Bayu Aji Pradana; Adhitya Bhawiyuga (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Internet of Things (IoT) devices are physical devices that are connected to each other through the internet. IoT devices have limitations on storage and computing capabilities so that various problems arise such as reliability, performance, scalability, security, and privacy. To overcome these problems, IoT devices can be integrated with cloud computing. However, from this integration there are other problems, namely the performance problem of computing due to the increasing number of connected devices, so a research is proposed in the form of developing IoT-Cloud by utilizing serverless computing. Serverless computing has auto-scaling capabilities so there is no need to manually re-adjust the server. The development of this platform is carried out in the cloud so that all parties who want to access must be connected to the internet and have a service account. GCP is used to build this platform, the features used are Authentication which serves to authenticate users, Functions in the form of a serverless framework that acts as a backend and subscriber, Firestore acts as a data storage place, and Hosting as a platform for deployment. Then there is Google Cloud IoT Core which acts as a broker so that IoT devices can send data to Google Cloud IoT Core which will then be channeled to subscribers. From the development tests that have been carried out, the results show that the platform can accept all incoming requests without any problems, this is due to the nature of serverless computing in the form of auto-scaling.